Characteristics and Determinants of Cassava Processed MSME Business Income - Dewa Aditya; Marlina Ekawaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Based on data obtained by the Communication and Informatics Office of Malang Regency in 2019 there were 319,061 MSMEs spread across Malang Regency and the largest MSMEs were engaged in agriculture, namely 76.76% or 244,934 business units. The large number of UMKM in agriculture in Malang Regency and the large number of agricultural productions, especially in cassava agricultural products, have made Malang Regency one of the largest producers of cassava in East Java, but the utilization and consumption of cassava production is still very low resulting in an excess supply. Of the total 249,445 tonnes produced by cassava farmers, the level of public consumption is only 24,337 tonnes. Therefore, in this study, the researcher intends to conduct an analysis of the characteristics and determinants of income from MSMEs processed by cassava in Malang Regency. Based on the theory of production and theory of human capital, there are several variables that influence the level of total revenue (Y), namely capital (X1), number of workers (X2), and use of information technology (X3). In the presence of several independent variables, the researcher uses multiple linear regression analysis techniques using classical assumption testing and hypothesis testing to find answers to existing problems.